The Federal Highway Administration, in partnership with the State of Iowa, for research on Portland Cement Concrete (PCC) pavements - Vanikar , Suneel (2025)
The Federal Highway Administration (FHWA) is partnering with the National Concrete Pavement Technology Center through a cooperative agreement. Initial research efforts will focus on damage estimation and the evaluation of materials used in the application of bonding surface layers.